Enhancing Students’ Writing Skills using Mind Mapping Strategy - Izzatul Laila; Teguh Sulistyo; Irma Lusia Apriliani; Izzatul Laila; Teguh Sulistyo; Irma Lusia Apriliani (Universitas Negeri Malang, 2023)
This study aimed to enhance students' writing skills by using mind mapping strategy. In order to enhance students' writing skills, teachers need to realize a strategy that is suitable with students' needs. A Collaborative Classroom Action Research (CAR), which was conducted in two cycles, was used in this study. Each cycle included the step of planning, acting, observing, and reflecting. The population of this research was the seventh-grade students of junior high school in the academic year of 2022/2023 consisting of 34 students. The average score of the preliminary study was 61, which was very low and below the expectations of the teacher and the students. After the implementation of the mind mapping strategy in two cycles, the students' writing scores improved. It can be seen from the average score of the students, which was 75 in the first cycle and 89 in the second cycle. In addition, the implementation of this strategy also received a positive response from the students based on the results of the attitude scale. It can be concluded mind mapping strategy can be used as a strategy to improve students' writing skills and students have a positive insight on this strategy